2016
DOI: 10.1038/mt.2015.216
|View full text |Cite
|
Sign up to set email alerts
|

Variable Virulence and Efficacy of BCG Vaccine Strains in Mice and Correlation With Genome Polymorphisms

Abstract: Bacille Calmette–Guérin (BCG), an attenuated strain of Mycobacterium bovis, is the only vaccine available for tuberculosis (TB) control. However, BCG is not an ideal vaccine and has two major limitations: BCG exhibits highly variable effectiveness against the development of TB both in pediatric and adult populations and can cause disseminated BCG disease in immunocompromised individuals. BCG comprises a number of substrains that are genetically distinct. Whether and how these genetic differences affect BCG eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 54 publications
4
90
0
3
Order By: Relevance
“…The majority (82%) of these absent epitopes are contained in 6 antigenic proteins encoded in RD1 and RD2 deleted in BCG strains. These and related studies further suggested that epitope sequence variation in BCG potentially affects human T cell recognition that could result in ineffective priming of the host immune system [16,17,[50][51][52].…”
Section: The Current Clinical Tb Vaccine Pipelinementioning
confidence: 90%
See 1 more Smart Citation
“…The majority (82%) of these absent epitopes are contained in 6 antigenic proteins encoded in RD1 and RD2 deleted in BCG strains. These and related studies further suggested that epitope sequence variation in BCG potentially affects human T cell recognition that could result in ineffective priming of the host immune system [16,17,[50][51][52].…”
Section: The Current Clinical Tb Vaccine Pipelinementioning
confidence: 90%
“…It is thought that over-attenuation of BCG due to loss of important immunodominant antigens (e.g. those in the region of difference 1 (RD1) region) in the process of its attenuation by repeated subcultivation passaging in nonstandardized conditions could be one of the reasons [16,17]. Moreover, large number of human clinical trials suggest that revaccination with BCG does not provide additional benefit, which could be due to preexisting heterologous immunity resulting from infection with nontuberculous environmental mycobacteria (NTM), a process known as masking and blocking [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, BCG (bacillus Calmette-Guérin), the only vaccine widely used against TB, provides varied protective efficacy (0-80% in randomized control trials) (3)(4)(5). Recently, the emergence of drug-resistant Mtb stains as well as HIV-TB co-infection poses numerous complexities for TB control (6,7).…”
Section: Tuberculosis (Tb) a Worldwide Infectious Disease Caused Bymentioning
confidence: 99%
“…In a study realized by Zhang et al (2016) assessing the virulence and efficacy of 13 BCG strains in SCID and BALB/c, showed that BCG strains of the DU2 group IV to which BCG-Phipps belongs, showed the highest levels of virulence among strains studied. They reported that these distinct levels of virulence could be explained by strainspecific duplications and deletions of genomic DNA.…”
Section: Cows Numbermentioning
confidence: 99%